Four-way handshake protocol for authenticating in multiple mix-zones - Senthil Kumar, T; Prabhakaran, S; Prashanth, V (International Journal of Engineering and Technology, 2018)
Authentication is the process of verifying that the users who they claim to be or not, it is based on identity and credentials. Most of the attacks can be reduced using authentication process. Authentication is important because as the amount of online data sharing has increased, threats and fraud in a large amount are also increased, a changing of the guard which provides security to mobile devices is needed for which authentication is necessary. Privacy of userâ€™s location is important in mobile networks, there are several strategies to protect the personal information (i.e., their location). In previous work it is introduced that the mix zone model which will change the old pseudonyms to new pseudonyms and anonymizes userâ€™s identity by restricting the position where users can be located. Later work, even in the multiple mix-zones model, attackers can attack by using side information (like footprints, navigation etc.). So, we need an authentication protocol while two mix-zones or user-services are communicating. We came across different authentication protocols like PAP, CHAP, and EAP. In this paper, a four-way handshake protocol is implemented for providing authentication while multiple mix-zones are communicating. A four-way handshake authentication protocol i.e., WPA-PSK protocol for verification. WPA-PSK is applied in such a way that both STA(supplicant) and AP(authenticator) can check that they are re-agreeing on a non-forged RSN and IE, therefore they are using the most secure available protocols.Â
Keywords: Authentication; Mobile Networks; Loca--Tion Based Service; Mix-Zone; Four-Way Handshake.